Factors associated with low health-related quality of life in persons with multiple sclerosis: A quantile-based segmentation approach. - Stefania Iaquinto; Benjamin Victor Ineichen; Anke Salmen; Jens Kuhle; Pascal Benkert; Lisa Hofer; Pasquale Calabrese; Christian P Kamm; Patrick Roth; Chiara Zecca; Sabin Ammann; Caroline Pot; et al. (PLoS ONE, 2024)
Background Improving health-related quality of life (HRQoL) is an important disease management goal in persons with Multiple Sclerosis (PwMS). HRQoL decreases with increasing age and prolonged disease duration; other factors remain less understood. Objective To identify associations of multiple sclerosis (MS) disease characteristics and symptom burden with low HRQoL. Methods Using the Swiss MS Registry, we applied quantile regression adjusted for age and MS disease duration to determine 25th (low HRQoL) and 75th (high HRQoL) percentiles of the EuroQol-5-Dimension (EQ-5D) distribution for PwMS. We compared PwMS across HRQoL groups by analyzing differences in sociodemographics, symptom burden, MS risk factors, gait impairment, and the MS Severity Score (MSSS), all measured at the same time as HRQoL. The analyses included descriptive methods, multivariable multinomial regression, and simultaneous quantile regression as a sensitivity analysis. Results We included 1697 PwMS with median age and time-to-diagnosis of 49 and 9 years. Multivariable regression revealed low HRQoL to be associated with receiving invalidity insurance benefits, reporting depression, muscle weakness, memory problems, pain, and severe gait impairment. The analysis for individuals with available MSSS (n = 937) showed an increasing probability of low HRQoL with higher MSSS. Conclusion Our segmentation method identified symptom burden and MS severity as factors associated with low HRQoL. Pharmacological and non-pharmacological MS symptom management, especially for depression, fatigue, pain, and muscle weakness, may warrant increased attention to preserve or improve HRQoL.